Spatial and Temporal Control of Senescence. Issue 11 (November 2017) - Ito, Yoko; Hoare, Matthew; Narita, Masashi
Abstract : Cellular senescence is an autonomous tumor suppressor mechanism leading to stable cell cycle arrest. Senescent cells are highly secretory, driving a range of different functions through the senescence-associated secretory phenotype (SASP). Recent findings have suggested that the composition of the SASP is dynamically and spatially regulated and that the changing composition of the SASP can determine the beneficial and detrimental aspects of the senescence program, tipping the balance to either an immunosuppressive/profibrotic environment or proinflammatory/fibrolytic state. Here, we discuss the current understanding of the temporal and spatial regulation of the SASP and the novel finding of NOTCH signaling as a regulator of SASP composition. Trends: NOTCH signaling is dynamically regulated during senescence. NOTCH1 signaling reciprocally regulates inflammatory cytokines and TGF-β during senescence. NOTCH1 signaling suppresses IL1α through downregulation of the transcription factor C/EBPβ. The NOTCH1-JAG1 pathway mediates cell–cell contact-dependent lateral induction of senescence.